(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2025)
Objective: To analyze the effects of the ATR training periodization method (accumulation, transformation, realization) on the physical form of university athletes, from the physical preparation and initial post-pandemic competitive period to a second continuous training process under normal sanitary conditions.Methodology: Pre-experimental, longitudinal, and comparative study of related samples. The sample consisted of 16 subjects aged 18 to 25, who were in an inactive training state before the intervention.Results: Between mesocycle 1 and mesocycle 2 of performance, athletes’ body composition improved significantly (p = 0.000809 and p = 0.000027). Strength training in power exercises, particularly the Clean and Jerk variants, showed significant improvement in both mesocycles (p = 0.000000). In the performance phase, pitchers exhibited significant progress between the two mesocycles (p = 0.000000). Regarding performance variables in competition, throwers increased their throwing distance, while sprinters and distance runners reduced their race times. Conclusion: The ATR periodization method proved to be an effective tool for structuring training loads across different periods. Additionally, its application resulted in significant and verifiable improvements in body composition and sports performance.